2019
DOI: 10.1002/jimd.12183
|View full text |Cite
|
Sign up to set email alerts
|

A study on a cohort of 301 Chinese patients with isolated methylmalonic acidemia

Abstract: Methylmalonic acidemia (MMA) is the most common organic acidemia in China. This study aimed to characterise the genotypic and phenotypic variabilities, and the molecular epidemiology of Chinese patients with isolated MMA. Patients (n = 301) with isolated MMA were diagnosed by clinical examination, biochemical assays, and genetic analysis. Fifty-eight patients (19.3%) were detected by newborn screening and 243 patients (80.7%) were clinically diagnosed after onset. Clinical onset ranged from the age of 3 days t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
27
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 41 publications
(29 citation statements)
references
References 50 publications
2
27
0
Order By: Relevance
“…Similar to the report by Hu et al 28 , in our population, c.323G>A was the most prevalent mutation in the MMUT gene. However, previous other studies have suggested that c.729_730insTT is the most common MMUT mutation in China 29,30 . This difference should be taken into account the small number of cases in this study and the impact of geographical differences.…”
Section: Discussionmentioning
confidence: 79%
“…Similar to the report by Hu et al 28 , in our population, c.323G>A was the most prevalent mutation in the MMUT gene. However, previous other studies have suggested that c.729_730insTT is the most common MMUT mutation in China 29,30 . This difference should be taken into account the small number of cases in this study and the impact of geographical differences.…”
Section: Discussionmentioning
confidence: 79%
“…Han et al described two patients, compound heterozygous condition with missense variants in combination with the c.1663G > A, one of which had mild hyperammonemia at presentation [17]. Kang et al also mentioned this mutation, however, without detailed description of the clinical information of the carrying patient [18]. Liu et al presented yet another case of compound heterozygous condition with a different mutation, who had a late symptomatic presentation at age 38 months with acute brain stem encephalitis and myelitis, a devastating complication of mut MMA [15].…”
Section: Discussionmentioning
confidence: 99%
“…In China, the most common mutations include c.729_730insTT(p.D244Lfs*39), c.1106G > A (p.R369H), c.323G > A (p.R108H), and c.1107dupT (p.T370Yfs*22) [8,14]. The c.1663G > A (p.A555T) mutation in the MMUT gene is relatively rare, which is so far reported only in a few cases [7,[15][16][17][18]. Limited information is available on the clinical and biochemical characteristics of patients carrying this mutation.…”
Section: Introductionmentioning
confidence: 99%
“…Metabolic therapy, including a high-calorie diet with special formula supplementation (no isoleucine, threonine, methionine, and valine), stopping protein intake and intramuscular cobalamin were provided to most patients. Treatment for the patients was then adjusted according to their response to vitamin B12 and other individual conditions 7 , 10 12 .…”
Section: Methodsmentioning
confidence: 99%